Perubahan Makna Teologis Sungai Kahayan Bagi Masyarakat Bukit Rawi - Yane Octavia Rismawati Wainarisi; Stynie Nova Tumbol (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
Dayak Ngaju tribe is a biggest tribe in Center Borneo. This tribe community have big interest to live in along of river Borders. It’s because this community hang all side of their life to the river. Kahayan Rivers as the target of research is a one of biggest river in Center of Borneo Abstract which have significant meaning for Kahayan community in economic, social so on theological perspectives. In the past, rivers reputed as connector between human and god. Because of this, Kahayan River became a place to do all local religion ritual from the pregnant time to the dead time of this tribe community. But since the development age, the are a meaning shift of theological meaning of Kahayan River for local people of Kahayan. This research made by qualitative study case approach to find the background of Theological meaning shift of Kahayan River for the people of Kahayan in Bukit Rawi Pulang Pisau Residence.